Dampak dari Penanganan Pandemi COVID-19 Terhadap Penanaman Modal Asing Langsung di Indonesia - Putri, Bianda Nathania (Legal Spirit, 2023)
Investment is an activity with the aim to seek long-term profits by buying stocks or securities. One of other types of investment is Foreign Direct Investment (FDI) which focused on investment activity to do business in a country carried out by foreign nationals with foreign capital or in partnership with domestic investors. FDI has many benefits for the host country and as the investing party, in the form of enriching the countries, industrial and technological progress, and increasing economic growth. But behind all benefits, in doing FDI there are risks that can be faced by foreign investors. These risks are triggered by political instability, inconsistency and incompetence of law enforcement, weak economy in a country, and can also be triggered by the spread of a disease on a massive scale. This research uses normative juridicial aapproach method and uses a qualitative approach. The result of this study shows that political, legal, and economic risks in a country have a negative impact on FDI and foreign investors. Furthermore, the COVID-19 pandemic and the handling by the Indonesian Government are in fact inconsistent and unresponsive which cause a domino effect on society, FDI, and also foreign investors.